EFL Teachers Critical Thinking Behaviors and the Challenges Facing them in Classrooms - Thouqan Saleem Yakoub Masadeh (Universitas Negeri Padang, 2021)
The main aim of the present study was to investigate EFL teachers critical thinking behaviors and the kinds of challenges they meet inside English language classrooms. A two-part questionnaire with twenty seven teaching behaviors and sixteen challenges was administered to sixty one Saudi EFL teachers at the secondary and intermediate teaching stages. Results showed that they regularly perform teaching behaviors that nurture their students' critical thinking skill. The most practiced behaviors were related to creating critical thinking-based student response while the least practiced behaviors were belonging to developing students' analysis and synthesis skills. Moreover, challenges related to English language school textbooks, classroom size, training and extra-curricular activities were all significant challenges that need urgent solutions.